A new approach to environmental education: The Ejoy-ME model in mangrove ecosystems - Riza Sativani Hayati; Destri Ratna Ma’rifah; Julia Astutik; I. Irmawanty (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
This study aimed to assess the effectiveness of Experiential and Joyful Learning Marine Edutourism (EJoy-ME) model to improving high school students’ environmental literacy, particularly their skills in analyzing environmental issues. The EJoy-ME model merges hands-on experiential learning and enjoyable learning experiences in real marine and mangrove ecosystem settings, with the goal of enhancing environmental awareness and encouraging pro-environmental behaviors. A quasi-experimental design was implemented with 85 tenth-grade students from Sekolah Indonesia Kuala Lumpur (SIKL) who participated at two marine ecotourism sites: Kuala Selangor Nature Park (KSNP) and Mangrove Point Klang River. The findings show that students taught using the EJoy-ME model had significantly greater improvements in environmental literacy in the “moderate” to “quite effective” range rather than the control group who was taught with a Problem-Based Learning (PBL) model. Student feedback further underscored the model’s effectiveness, as learners reported very positive experiences in terms of joyful learning, experiential engagement, and environmental education quality. This approach effectively engaged students to form a deeper emotional connection toward environmental issues. This study contributes to the field of environmental education by showcasing the potential of an ecotourism-based experiential learning model to foster environmental literacy.